Rain Detector for Cloth Hanger - Syamim Daud; Hikma Shabani (Progress in Engineering Application and Technology, 2022)
Most people nowadays spend less time at home. As a result, a rain detector for cloth hanger is useful in our daily lives. A cloth drying system is designed in this project, which can automatically collect hanging clothing when it rains and then retrieve them out again when the sun shines. The system is controlled by a Node MCU Esp8266, which includes a rain sensor for detecting rain sensor for detecting the rain. A DC motor was used to convert electrical energy into mechanical energy for the movement of the retractable cloth drying device. This system can withstand wet clothes.